African Regional Jurisdiction. How African Union is creating and Innovative Regional Jurisdiction for International Crimes - Garrido, R. (PoLaR: Portuguese Law review, 2020)
The International Criminal Court (ICC), based in The Hague, the Netherlands, is the result of the will of mankind to trial the most serious crimes committed in times of war, and usually committed with systematic and generalized violence. The ICC results from the experience of several ah hoc tribunals that took place in the 20th Century. The special military court previewed in the Versailles Treaty, after I World War, was designed to trial the former German Emperor, William II of Hohenzollern, for the “supreme offence against international morality and the sanctity of treaties”1. After the II World War, two tribunals were set up to trial the crimes committed by the Nazis and the Japanese, respectively, the Tribunals of Nuremberg and Tokyo. In the end of the 20th Century, the War in Bosnia-Herzegovina and the genocide of Rwanda lead to two ad hoc tribunals, to trial the crimes committed the mass human rights violations committed in those periods. In 1998, it was adopted the Rome Statute for the International Criminal Court, that marks a new era in international criminal law. A permanent court was set up with the Rome Statute.